Solidification and homogenization behaviors of Al-9.1 Zn-2.1 Mg -2.2 Cu-0.1 Zr-0.07 Ce alloy - Xinxiang Yu; Jie Sun; Zhutie Li; Caiqiong Li; Wenwen Liu; Pengcheng Zhu; Zhigang Yu (Materials Research Express, 2018)
Solidification and homogenization behaviors of Al-9.1Zn-2.1Mg-2.2Cu-0.1Zr-0.07Ce (wt%) alloy were investigated. Obvious grain refinement was observed in as-cast alloy by Ce modification, the main mechanism of the grain refinement is that the redistribution of solute during solidification leads to the increase of the supercooling degree of the solid/liquid interface front component and the blocking effect of primary Ce enrichment phase. Serious non-equilibrium eutectic phase (Mg(Zn, Al, Cu) _2 ) segregation existed mainly along the grain boundary after cast. The solidification segregate phase dissolved into α (Al) matrix gradually during homogenization and a phase transformation from Mg(Zn, Al, Cu) _2 to few Al _2 CuMg were also occurred even with 9.1 wt% Zn content at present alloy, owing to trace Ce as solute can hinder the diffusion of Cu atoms in Mg(Zn, Al, Cu) _2 phase effectively. Obviously the solidification Mg(Zn, Al, Cu) _2 phase was eliminated thoroughly and a larger number of disperse Al _3 Zr was precipitated effectively by a double-stage homogenization treatment. Thus the homogenization at 435 °C for 8 h and then at 470 °C for 32 h is identified as an optimum homogenization treatment in this experimental alloy.